2019
DOI: 10.1111/1759-7714.13237
|View full text |Cite
|
Sign up to set email alerts
|

Advance directives of lung cancer patients and caregivers in China: A cross sectional survey

Abstract: Background: This study aimed to investigate lung cancer patients and attitudes of their caregivers toward advance directives (ADs) in China. Methods: A cross sectional study was conducted in the Department of Oncology outpatient clinic in West China Hospital, Sichuan University. A questionnaire was used to survey the attitudes of lung cancer patients and caregivers toward ADs. Results: A total of 148 lung cancer patients and 149 caregivers were enrolled into the study. Of these, 94.6% and 89.9% of patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
1
11
0
4
Order By: Relevance
“…Among them, lung cancer occupies the top spot due to its high morbidity and mortality. It is estimated that by 2025, there will be 1 million lung cancer patients in China (Sun et al, 2020;Feng et al, 2020;Xing et al, 2019). Therefore, lung cancer has replaced cardiovascular disease as the biggest factor threatening the safety of national survival.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, lung cancer occupies the top spot due to its high morbidity and mortality. It is estimated that by 2025, there will be 1 million lung cancer patients in China (Sun et al, 2020;Feng et al, 2020;Xing et al, 2019). Therefore, lung cancer has replaced cardiovascular disease as the biggest factor threatening the safety of national survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, The study indicated that relatively few aged citizens completed the forms due to lacing Internet technology abilities as the ‘Five Wishes’ forms were online and digital [ 24 ]. Furthermore, Chinese scholars conducted cross-sectional studies on the recognition, acceptance, knowledge, attitude and practice (KAP) of ADs using self-designed questionnaires among terminally ill patients, older adults and health professionals [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Overall, the recognition, acceptance, knowledge and KAP of ADs among the population improved over time [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chinese scholars conducted cross-sectional studies on the recognition, acceptance, knowledge, attitude and practice (KAP) of ADs using self-designed questionnaires among terminally ill patients, older adults and health professionals [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Overall, the recognition, acceptance, knowledge and KAP of ADs among the population improved over time [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. And health care professionals had a higher recognition and acceptance of ADs, better KAP of ADs compared with the other groups at the same time period [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study clarified attitudes and preferences toward ACP in a relatively Chinese large sample mostly in tertiary hospitals but did not involve the elderly population in the primary medical and health care institution and the influence of functional status on ACP attitudes. Prior research has compared attitudes toward ACP between patients and family members, which has focused on specific diseases such as cancer and heart failure (13,14). Different from the other specialized wards with a certain specific disease, older patients in the geriatric wards in the primary medical and health care institution, may have advanced age, complex multimorbidity, multiple functional loss, and a higher proportion at the final stage of the disease.…”
Section: Introductionmentioning
confidence: 99%